Assessment and Correction of the Cardiac Complications Risk in Non-cardiac Operations - What's New? - A. N. Sumin (Столичная издательская компания, 2022)
Cardiovascular complications after non-cardiac surgery are the leading cause of 30-day mortality. The need for surgical interventions is approximately 5,000 procedures per 100,000 population, according to experts, the risks of non-cardiac surgical interventions are markedly higher in the elderly. It should be borne in mind that the aging of the population and the increased possibilities of medicine inevitably lead to an increase in surgical interventions in older people. Recent years have been characterized by the appearance of national and international guidelines with various algorithms for assessing and correcting cardiac risk, as well as publications on the validation of these algorithms. The purpose of this review was to provide new information about the assessment and correction of the risk of cardiac complications in non-cardiac operations. Despite the proposed new risk assessment scales, the RCRI scale remains the most commonly used, although for certain categories of patients (with oncopathology, in older age groups) the possibility of using specific questionnaires has been shown. In assessing the functional state, it is proposed to use not only a subjective assessment, but also the DASI questionnaire, 6-minute walking test and cardiopulmonary exercise test). At the next stage, it is proposed to evaluate biomarkers, primarily BNP or NT-proBNP, with a normal level - surgery, with an increased level - either an additional examination by a cardiologist or perioperative troponin screening. Currently, the prevailing opinion is that there is no need to examine patients to detect hidden lesions of the coronary arteries (non-invasive tests, coronary angiography), since this leads to excessive examination of patients, delaying the implementation of non-cardiac surgery. The extent to which this approach has an advantage over the previously used one remains to be studied.